MODELS OF ORGANIZATIONAL CULTURE OF THE ENTERPRISE IN THE CONTEXT OF DESTRUCTIVE CHANGES (Economic journal of Lesya Ukrainka Volyn National University, 2021)
Under the organizational culture is understood the way in which management seeks to understand the tasks Understanding the organizational culture of the enterprise and its climate, how employees evaluate themselves, the company and its future can predict the efficiency of the enterprise, sources of success and failure. The purpose of the article: to assess the existing and desired model of organizational culture based on the opinions of employees of Ukrainian enterprises and to diagnose the impact of the model declared as "existing at the moment" on the scale of destructive changes in enterprises.It is noted that the model of organizational culture is one of the indicators of its comprehensive assessment, on the basis of which the strategy of its development is developed. The study was conducted on the basis of the model of organizational culture K.S. Cameron and R.E. Quinn.The analysis of the collected material showed that the dominant model of organizational culture - mentioned by the respondents as "existing" is hierarchical (37.2%) and market (31.2%). However, the most desirable was the clan model (46.7%), and the least desirable - the market (14.7%). This result indicates that the characteristics inherent in the model of market culture do not find support among employees. The features of the clan's culture are relevant for them: friendly atmosphere, mutual support, teamwork, good leader.It is established that in enterprises with a market and hierarchical model of culture destructive changes are at the highest level. This is professional burnout, overload of responsibilities, fear of punishment in case of resistance. Here the most common phenomena are called nepotism, organizational schizophrenia and fragmentation. These models are typical for most of the surveyed companies.It is substantiated that, on the one hand, organizational culture can be a creative tool of creative work, where employees feel happy, on the other hand, it can have a destructive effect on the formation of the work environment. It is established that the form of organizational culture depends primarily on the level of professionalism of management. It plays a key role in creating a model of organizational culture.
Keywords: destructive changes, dualism of organizational culture, models of organizational culture K.S. Cameron and R.E. Quinn, existing and desirable models of organizational culture.